Diketopiperazines from Rhabdastrella globostellata. (25th October 2022) - Trang, Do Thi; Dung, Duong Thi; Hang, Dan Thi Thuy; Dung, Nguyen Viet; Linh, Tran My; Mai, Nguyen Chi; Yen, Pham Hai; An, Do Hoai; Nhiem, Nguyen Xuan; Van Kiem, Phan; Tai, Bui Huu
Abstract: From the methanol extract of the Vietnamese marine sponge Rhabdastrella globostellata (Carter, 1883), four diketopiperazines (1 ‐4 ) and one indol alkaloid (5 ) were isolated by various chromatographic methods. Their chemical structures were identified to be cyclo‐(L‐Pro‐L‐Ile) (1 ), cyclo‐(L‐Pro‐L‐Leu) (2 ), cyclo‐(D‐Pro‐L‐Ile) (3 ), cyclo‐(L‐Pro‐L‐Phe) (4 ), and tryptophol (5 ) by using a combination of ESI‐MS, 1D and 2D NMR spectral data as well as by comparison with previous literature. This is the first report of these compounds from Rhabdastrella globostellata . Abstract :